Ultrastructural Analysis of Cells From Bell Pepper (Capsicum annuum) Infected With Bell Pepper Endornavirus - Otulak-Kozieł, Katarzyna; Kozieł, Edmund; Escalante, Cesar; Valverde, Rodrigo A. (Frontiers in Plant Science, 2020)
Endornaviruses include viruses that infect fungi, oomycetes, and plants. The genome of plant endornaviruses consists of linear ssRNA ranging in size from approximately 13-18 kb and lacking capsid protein and cell-to-cell movement capability. Although, plant endornaviruses have not been shown to cause detectable changes in the plant phenotype, they have been associated with alterations of the host physiology. Except for the association of cytoplasmic vesicles with infections by Vicia faba endornavirus, effects on the plant cell ultrastructure caused by endornaviruses have not been reported. Bell pepper endornavirus (BPEV) has been identified in several pepper (Capsicum spp.) species. We conducted ultrastructural analyses of cells from two near-isogenic lines of the bell pepper (C. annuum) cv. Marengo, one infected with BPEV and the other BPEV-free, and found cytopathology associated with BPEV-infections. Some cells of plants infected with BPEV exhibited alterations of organelles and other cell components. Affected cells were located mainly in the mesophyll and phloem tissues. Altered organelles included mitochondrion, chloroplast, and nucleus. The mitochondria from BPEV-infected plants exhibited low number of cristae and electron-lucent regions. Chloroplasts contained plastoglobules and small vesicles in the surrounding cytoplasm. Translucent regions in thylakoids were observed, as well as hypertrophy of the chloroplast structure. Many membranous vesicles were observed in the stroma along the envelope. The nuclei revealed a dilation of the nuclear envelope with vesicles and perinuclear areas. The organelle changes were accompanied by membranous structure rearrangements, such as paramural bodies and multivesicular bodies. These alterations were not observed in cells from plants of the BPEV-free line. Overall, the observed ultrastructural cell alterations associated with BPEV are similar to those caused by plant viruses and viroids and suggest some degree of parasitic interaction between BPEV and the plant host.